Jejak Seni Pertunjukan dalam Hikayat Banjar: Silang Budaya Jawa dan Banjarmasin - Naufal Anggito Yudhistira (Jurnal Kajian Seni, 2022)
Abstract Hikayat Banjar contains traces of ancient arts around Banjar kingdom. In this work, the poet states that the customs in Banjar have their roots in Majapahit in many times. The artistic traces of this text also show a connection with Javano-Balinese art. The aims of this research to reveal the past art forms that contained in Hikayat Banjar and see their relationship with Javanese art. The approach of this research is culture as text. In Hikayat Banjar there are various types of traditional music, dance, and traditional drama. These art forms show a similar pattern with Javanese and Balinese art, especially from the palace. These performing art in Hikayat Banjar show the relationship between Banjarese and Javanese arts. From a musical point of view, gamelan in Hikayat Banjar is closely related to the karawitan tradition in Javanese courts. The dance in Hikayat Banjar shows similarities to the wireng genre in Java. The form of theatre in the Hikayat Banjar separated in two kinds, the drama that played by humans and puppets. This traditional theatre form has a close relationship with Javanese and Balinese arts in the past. Despite having the same artistic roots as Java and Bali, the arts in Banjar developed in the different situations and conditions. The relationship between Javanese and Banjar arts also related to the migration from Java to Banjarmasin in the 17th century.Keywords: Hikayat Banjar, performing art, karawitan, dance, traditional theatre. AbstrakHikayat Banjar memuat jejak kesenian kuno Banjar dan sekitarnya. Dalam karya ini, penyair berkali-kali menyatakan bahwa adat di Banjar berakar dari Majapahit. Jejak kesenian dari teks ini juga menunjukkan adanya kaitan dengan kesenian Jawa dan Bali. Penelitian ini bertujuan untuk mengungkap bentuk kesenian masa lalu yang tertuang dalam Hikayat Banjar dan melihat kaitannya dengan kesenian Jawa. Penelitian ini berpegang pada pendekatan bahwa kebudayaan adalah teks. Dalam Hikayat Banjar terdapat berbagai jenis karawitan, tari, dan drama tradisi. Bentuk-bentuk kesenian itu menunjukkan adanya kesamaan pola dengan kesenian Jawa dan Bali, khususnya dari lingkungan istana. Jejak-jejak itu menunjukkan hubungan antara kesenian Banjar dengan Jawa. Dari segi seni musik, gamelan di Hikayat Banjar terkait erat dengan tradisi karawitan di istana-istana Jawa. Seni tari dalam Hikayat Banjar menunjukkan kemiripan dengan genre tari wireng di Jawa. Bentuk teater dalam teks Hikayat Banjar ada yang dimainkan oleh manusia dan ada yang menggunakan wayang. Bentuk teater tradisi itu memiliki kedekatan dengan kesenian Jawa dan Bali pada masa lampau. Walaupun memiliki kesamaan akar kesenian dengan Jawa dan Bali, kesenian di Banjar berkembang mengikuti situasi dan kondisi yang berbeda. Pertalian kesenian Jawa dan Banjar terkait dengan adanya perpindahan penduduk dari Jawa ke Banjarmasin pada abad ke-17.Kata Kunci: Hikayat Banjar, seni pertunjukan, karawitan, tari, drama tradisional.